2018
DOI: 10.1101/300590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Biotic interactions limit the geographic range of an annual plant: herbivory and phenology mediate fitness beyond a range margin

Abstract: Original research letterWord count: Abstract (144), Main text (4929) Number of references: 61 Number of figures: 4We confirm that, should the manuscript be accepted, the data supporting the results will be archived in an appropriate public repository.2 Abstract Species' range limits offer powerful opportunities to study environmental factors regulating distributions and probe the limits of adaptation. However, we rarely know what aspects of the environment are actually constraining range expansion, much less w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 59 publications
(79 reference statements)
0
6
0
Order By: Relevance
“…In arid regions like those inhabited by xantiana, plants can avoid periods of low water availability late in the growing season by shifting phenology and flowering earlier (Aronson, Kigel, Shmida, & Klein, 1992;Volis, 2007). For example, Lau and Lennon (2012) showed that the microbial community of the annual plant, (Benning, Eckhart, Geber, & Moeller, 2018). Our results suggest that microbial communities may play an important role in modulating the expression of this ecologically important trait.…”
Section: Plant Responses To Amfmentioning
confidence: 67%
See 1 more Smart Citation
“…In arid regions like those inhabited by xantiana, plants can avoid periods of low water availability late in the growing season by shifting phenology and flowering earlier (Aronson, Kigel, Shmida, & Klein, 1992;Volis, 2007). For example, Lau and Lennon (2012) showed that the microbial community of the annual plant, (Benning, Eckhart, Geber, & Moeller, 2018). Our results suggest that microbial communities may play an important role in modulating the expression of this ecologically important trait.…”
Section: Plant Responses To Amfmentioning
confidence: 67%
“…Earlier flowering time in xantiana is favored by selection in some environments (Geber and Eckhart 2005), in part because flowering time strongly influences a plant's probability of fatal mammal herbivory in some parts of xantiana’ s range. For example, at the edge of xantiana 's range, each day delay in flowering increases a plant's odds of fatal herbivory by 5%, and this fatal mammal herbivory can have large effects on population growth rates (Benning, Eckhart, Geber, & Moeller, ). Our results suggest that microbial communities may play an important role in modulating the expression of this ecologically important trait.…”
Section: Discussionmentioning
confidence: 99%
“…In some other cases, the research focus has been on the seasonal phenology of herbivorous insects adjusting to that of the host plant (Chuine, 2010 ; Elzinga et al, 2007 ; Singer & Parmesan, 2010 ). In a context of mammalian herbivory, Benning et al ( 2018 ) cite a case of a plant's reproductive phenology constraining its geographic range.…”
Section: Introductionmentioning
confidence: 99%
“…Elzinga et al 2007;Chuine 2010;Singer and Parmesan 2010). In a context of mammalian herbivory, Benning et al (2018) cite a case of a plant's reproductive phenology constraining its geographic range. Despite these considerations, the possible extent and diversity of putative biotic factors as evolutionary drivers of seasonal plant phenology appear to remain under-researched, especially with pathogens.…”
Section: Introductionmentioning
confidence: 99%